Comparing the Effect of Public and Private Health Expenditures on the Health Status of D-8 Countries - Sepideh Arab; Ebrahim Ghaed; Atefeh Mazinani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study uses the Panel Data model to compare the effect of public and private health expenditures on the health status of D-8 member countries from 2020 to 1995.Methodology: The statistical population studied in this research includes research from D-8 group member countries. Time series information about these countries was collected from reputable international sources, including the World Bank, which, using Eviews software, was tested. Variables used in this study include health status (infant mortality rate), human capital, economic growth, public health expenditures, private health expenditures, and urbanization rates.Findings: The study's results indicate a significant negative effect of public and private health costs on infant mortality. Still, the impact of public spending has been more substantial than the private sector. In other words, allocating the government budget significantly impacts the health sector more than the private sector in reducing infant mortality, health expenditures, and urbanization rates. It can be argued that increasing public health care costs can significantly improve health and accelerate development goals to reduce infant mortality in these countries.Originality/Value: The present study showed that public health costs in this group of countries have a more significant effect than other model variables in reducing neonatal mortality, which could be a vital factor in improving health states and even the distribution of resources